تأثير الرش الورقي ببعض العناصر النادرة ((B,Zn,Fe في الإزهار والعقد لأشجار الليمون الحامض صنف الماير (Latakia University Journal -Biological Sciences Series, 2018)
The experiment was carried out during the two seasons of 2015 and 2016 in a citrus lemons orchard in Lattakia province, the area of ​​the kalouf on Mayer trees nine years old, with the aim of studying the effect of foliar spraying with boron, zinc and iron on flowering and fruit set. These were isolated and combined on the Mayer trees with 0.5 cm3/liter boron oxide, zinc chelate( 0.05 g / liter), iron chelate (1g / liter) and two elements together (iron chelate + boron oxide), (iron chelate + zinc chelate), (Boron oxide + zinc chelate), or the three elements together (iron chelate + boron oxide + zinc chelate). In the same concentrations applied to single spray. The pollen vitality, the percentage of ovary abortion, the proportion of hermaphrodite flowers, the average number of total and set  flowers, and the percentage of the initial and final setting were calculated in both seasons. The results showed a significant increase in the percentage of live pollen in the treatments that contained boron compared to other treatments. The treatment of B + Fe gave the highest percentage of 94.81%, followed by( B,Zn,Fe) treatment 92.23% as the average of the two seasons .There was also a decrease in the percentage of ovarian abortions, an increase in the percentage of hermaphrodite flowers in boron spraying and the highest percentage achieve(82.88%) when treated with zinc chelate and boron oxide as the average of the two seasons. As a result of the statistical analysis of the percentage of hermaphrodite flowers, there were differences between all the studied treatments with the superiority of the spraying treatment of boron and zinc in the two seasons on the rest of the transactions. As for the fruit set percentage, shows the superiority of the spraying treatment with boron, zinc and iron on the rest treatments.                                                                نفذت التجربة خلال موسمي (2015 و 2016) في بستان حمضيات ( ليمون حامض) في محافظة اللاذقية قرية القلوف على صنف الماير بعمر تسع سنوات بهدف دراسة تأثير التغذية الورقية بعناصر (البورون والزنك والحديد) في الإزهار والعقد. رشت هذه العناصر منفردة ومجتمعة على أشجار الماير بصورة أكسيد البورون 0.5 سم3 / ليتر،  شيلات الزنك 0.05 غ/ليتر ، شيلات الحديد (1غ/ليتر ) بعنصر منفرد، وبعنصرين معاً(شيلات الحديد+ أكسيد البورون )، (شيلات الحديد +شيلات الزنك)، (أكسيد البورون + شيلات الزنك)، أو بالعناصر الثلاثة معاً (شيلات الحديد+ أكسيد البورون + شيلات الزنك) .  و بالتراكيز نفسها المطبقة بالرش المنفرد . حسبت كلاً من حيوية حبوب الطلع ونسبة المبايض المجهضة ونسبة الأزهار الخنثى ومتوسط عدد الأزهار الكلية والعاقدة ونسبة العقد الأولي في الموسمين . لوحظ زيادة في جميع المؤشرات المدروسة في المعاملات المرشوشة مقارنة بالشاهد  ، إذ أظهرت النتائج زيادة واضحة في نسبة حبات الطلع الحية في المعاملات التي احتوت على عنصر البورون مقارنة بالمعاملات الأخرى ، وأعطت معاملة ((B+ Fe أعلى نسبة 94.81% تلتها المعاملة بالبورون والحديد والزنك % 92.23 كمتوسط موسمين. لوحظ أيضاً انخفاض في نسبة المبايض المجهضة و زيادة في  النسبة المئوية للأزهار الخنثى عند الرش بالبورون وأعلى نسبة تحققت للأزهار الخنثى  (82.88)%عند المعاملة بشيلات الزنك والبورون كمتوسط موسمين . وبنتيجة التحليل الإحصائي لنسبة الأزهار الخنثى تبين وجود فروق بين جميع المعاملات المدروسة مع تفوق معاملة الرش بالبورون والزنك في الموسمين على باقي المعاملات. أما بالنسبة لنسبة العقد فقد تفوقت المعاملة بالبورون والحديد والزنك على باقي المعاملات.